Does repeated dry sauna bathing change thermoregulation process in elite cross country skiers? - Drzazga, Z.; Binek, M.; Pokora, I. (Journal of Thermal Analysis and Calorimetry, 2021)
The aim of this study was to evaluate the influence of a series of ten finnish dry sauna bathing on skin temperature following exercise test for elite cross-country skiers and test, if the regular sauna baths induce any changes in physiological or haema-tological parameters in elite athletes. Ten elite cross-country skiers (21.7 ± 3.1 years, height: 1.79 ± 0.025 m, body mass: 71.06 ± 4.77 kg) participated in this study. They performed two continuous exercise tests, before and after a series of ten sauna baths. During experiment, the superficial temperature distributions, physiological and haematological parameters were meas-ured. The marked temperature drop was visible in upper body and smaller in lower part of body after exercise test. 10 min after experimental exercise test slow return of the skin temperature to pre-workout values was observed in lower limbs unlike upper part of body. Results of this study indicated that passive induced heat acclimation have a moderate, positive effect (above 2%) on plasma volume and a small impact on physiological and temperature responses to exercise in elite athletes. We conclude that ten finnish dry sauna baths can induce weak changes in the superficial temperature distributions following exercise test, a certain decrease in resting heart rate and small increase in plasma volume in the elite cross-country skiers.